Performance and robustness analysis for structured uncertainty - Doyle, John C.; Wall, Joseph E.; Stein, Gunter (1982 21st IEEE Conference on Decision and Control, 1982)
This paper introduces a nonconservative measure of performance for linear feedback systems in the face of structured uncertainty. This measure is based on a new matrix function, which we call the Structured Singular Value.